PERAN BAHASA INDONESIA DALAM MEMBANGUN KOMUNIKASI EFEKTIF ANTARA KONSELOR DAN KLIEN - sari, Yuliana; Novandi, Putra Teguh; Rizqi, Nabila Dhiyaa; Afifa, Naila Aulia; Simanjuntak, Natanael; Saragih, Kevin Pardomuan; Setianta, Maykel Putra (Jurnal Keluarga Sehat Sejahtera, 2024)
Indonesian has an important role in building effective communication between counselors and clients during the guidance and counseling process. Effective communication not only includes delivering a message clearly but also involves empathy, attention, and understanding of the client's background. The straightforward and easy-to-understand use of Indonesian helps create a comfortable atmosphere for clients, so they are more open in expressing problems. In a multicultural context, Indonesian functions as a unifying tool that minimizes communication obstacles due to regional language differences, creating an inclusive and supportive environment. Additionally, non-verbal communication such as facial expressions, eye contact, and body language strengthens the relationship between counselors and clients. This study uses the Systematic Literature Review (SLR) method to identify the role of Indonesian in counseling. The results of the study show that a combination of effective verbal and non-verbal communication and sensitivity to the client's culture can improve the quality of the counseling process. In conclusion, optimizing the use of Indonesian in counseling is able to support clients to understand themselves, solve problems, and develop their potential to the maximum.